The Effectiveness of a Mobile Learning Environment in Improving Psychological Security in Blind Students - Amr El Koshiry; Entesar Eliwa; Tarek Abd El-Hafeez; Mohamed Abd Allah Tony (Scientifica)
This study aimed to investigate the impact of the Edmodo mobile learning environment on promoting psychological security among university students with visual impairments, at both the undergraduate and postgraduate levels. The researchers employed a combination of descriptive and quasiexperimental methodologies. The primary study sample consisted of 20 visually impaired students from Beni Suef University, divided equally between an experimental group (10 students) and a control group (10 students). To achieve the research objectives, the Psychological Security Scale was utilized and the experimental group received an intervention involving the implementation of a mobile learning environment using Edmodo. The data analysis revealed a statistically significant difference between the experimental and control groups in the postassessment, with the experimental group demonstrating an elevated sense of psychological security. Furthermore, the experimental group showed significant improvements in the pre- and postassessments, favoring the latter, with a standard score of 3.781. No significant differences were observed between the postassessment and the follow-up evaluation of the experimental group, with a standard score of 0.471, indicating the continuous effectiveness of the Edmodo mobile learning environment in enhancing the psychological security of visually impaired university students. This efficacy was sustained even one month after the student’s graduation, as evidenced by the follow-up assessment.